Integrative Morality Paradigm as an Alternative For Dichotomous Religion and Science in Education - Maksudin, Maksudin (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Nowadays, the problems of the field of education are getting wider and more tragic. The root cause of those problems is moral decadence caused by a dichotomous morality. It means that there is a difference, separation, and contradiction between religion and science. Morality is a moral system that exists in ideas, attitudes, and human activities. An integrative morality paradigm based on religion and natural law is necessary to avoid a dichotomy between the two. This study is a literature study using a descriptive-qualitative approach. This study shows that the new paradigm considered relevant is an integrative paradigm of morality between religion and science, which leads to an integrative morality in the form of moral systems. The idea, attitude, and human activity are built on an integrative morality through a dialectical approach. Religion and science are like two sides of a coin that cannot be separated. There is also a similar relationship between religion and morality and between morality and science. Humans learn from sunnatullah through observations, experiments, explorations, and elaboration, then present and discover science. At the same time, morality is based on human nature itself. In conclusion, an integrative morality paradigm can integrate religious and scientific understanding to avoid a dichotomy between religion and science.